Midwives’ Views Regarding Tuberculosis Screening amongst HIV/AIDS Positive Pregnant Women South Africa - Violet Manonyana Chewe; Sisinyana Hannah Khunou (STIKes Patria Husada Blitar, 2023)
Tuberculosis (TB) infections is classified as one of the non-pregnancy related infections (NPRI) which cause maternal mortality. Therefore, it was important for the researcher to explore the challenges faced by midwives regarding TB screening as it is the most leading complication in human immunodeficiency virus (HIV) infected pregnant women. To that effect, several strategies for TB screening during pregnancy have been introduced and implemented thus far. Screening of TB during antenatal care helps to enhance early detection, exclusion and treatment of the infection in pregnant women who are HIV positive. The study used qualitative descriptive research design. The population included all midwives aged 30 to 48 years, who were working at primary health (PHC) clinics in Kganya local area, Capricorn District, Limpopo Province in South Africa. Nonprobability purposive sampling technique was employed to select ten midwives. Data were collected through in-depth individual semi -structured interviews with ten midwives. Data analysis was accomplished, using the manual thematic analysis according to Tesch’s method of data analysis. Finally the main themes were extracted. Two themes emerged from the study, namely: Challenges regarding TB screening; Measures that can enhance TB screening. It is important that the department of health should pay attention to challenges faced by midwives to ensure adequate TB screening amongst HIV positive pregnant women. Capacitating both midwives and the community with knowledge regarding TB screening during pregnancy can be beneficial to the health of the pregnant women and their unborn babies.